Ethnic identities, sense of belonging and the significance of sport: stories from immigrant youths in Germany. Issue 3 (3rd July 2017) - Burrmann, Ulrike; Brandmann, Katrin; Mutz, Michael; Zender, Ursula
Abstract: Germany is becoming a multicultural society with a growing migrant population. Issues of social integration and societal cohesion are ongoing themes in public debates. In this regard, sport is often considered as a tool for fostering integration and a sense of belonging among migrants. This paper uses a qualitative methodology to explore the complex and multilayered entanglements and intersections between sports activities and feelings of belonging. Four case studies illustrate that sport can have manifold meanings and consequences for young people. It may work as means of emancipation (Büsra's story), but also reassert traditional values (Nasan's story). It can stabilize and provide hold in times of insecurity (Dejan's story) and may work as a source for reputation and respect in a disadvantaged social milieu (Youssuf's story). However, all four case studies highlight the ambivalence and inner conflicts that these immigrant youths have to face in sport and society. Moreover, they suggest that it is not sport per se, but the experiences of success and self-efficacy that result from athletic talent in combination with positive social interactions with 'significant others' in sport that matter.